Trends and Impacts of In-Migration in Birendranagar Municipality Surkhet - Dhakal, Bed Prakash (Spectrum of Humanities and Social Sciences, 2025)
In-migration in Birendranagar Municipality, Surkhet, has become a prominent urbanization trend with significant socio-economic implications. This study aims to investigate the patterns, causes, and impacts of in-migration in this rapidly growing area. Using a descriptive research design and quantitative methods, the study employs non-probability, purposive sampling to select participants. Data collection was based on field observations to analyze migration patterns and socio-economic characteristics. Findings indicate that the majority of migrants 56% come from neighboring hilly districts like Dailekh and Salyan while 42% originate from mountain zones such as Mugu, Humla, and Kalikot. Primary push factors include the lack of education (35%), unemployment (19%), unproductive soil (16%), and inadequate healthcare and transportation (16%). Additionally, 17% of migrants were displaced due to the Maoist insurgency in their home regions. The influx of migrants has led to the creation of new settlements, fostering urban growth but also bringing challenges such as environmental degradation and limited social services. Migrants face economic hardship, with 28% reporting financial strain due to low-income jobs and high urban living costs. Social challenges, including cultural differences and integration issues, affect 27% of migrant households. The study highlights the predominance of male migrants with higher educational and occupational status compared to females. It also emphasizes the crucial role of education, employment, and infrastructure in attracting migrants to Birendranagar, Surkhet. The findings underline the need for strategic urban planning and policy interventions to manage migration effectively. Addressing both the causes and consequences of in-migration will ensure sustainable development, improve resource distribution, and foster better integration of migrants into the urban environment.